Pengaruh Budaya Organisasi dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Melalui Kepuasan Kerja (Studi Kasus Pada PT. Artajasa Pembayaran Elektronis) - Aploegi, Sophie Andriani; Nuraeni, Nuraeni; Hasanah, Hasanah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This research is entitled "The Influence of Organizational Culture and Leadership Style on Employee Performance Through Job Satisfaction (Case Study at PT. Artajasa Pembayaran Elektronis)". The method for collecting data in this research was carried out by distributing questionnaires to 195 employee respondents of PT. Artajasa Pembayaran Elektronis. This research method used a quantitative method that is associative in nature using primary data. The results of this research show that organizational culture has no significant effect on employee performance, leadership style has a significant effect on employee performance, organizational culture and leadership style have a significant effect on job satisfaction, job satisfaction has a significant effect on employee performance, organizational culture and leadership style have a significant effect on employee performance through job satisfaction.